Transformasi Sintesis Data Kualitatif Menjadi Analisis Meta Data Tentang Manajemen Akuntansi Lingkungan - Octavia Diana Monica Tuegeh; Adrian Nagy; Johan Reineer Tumiwa (Jurnal Akuntansi Manado (JAIM), 2024)
This study aims to transform the synthesis of qualitative data into quantitative analysis through a meta-analytic approach in environmental management accounting. With the growing global attention towards environmental issues, companies face challenges in reducing their carbon footprint and enhancing energy efficiency. This research identifies and analyzes corporate strategies to achieve these objectives and evaluates their long-term sustainability. Additionally, it explores the adoption of innovative technologies such as IoT and AI in environmental management accounting and examines the impact of environmental policies on corporate accounting practices. Through a meta-analysis of 359 articles from various academic databases, it was found that innovative technologies significantly enhance environmental management, and stringent environmental policies promote corporate sustainability practices. This study contributes theoretically by integrating technological innovations into environmental accounting practices and developing a new analytical model. Future research directions include longitudinal studies, contextual analysis, and the development of sustainability performance indicators.